Acupuncture might enhance word recognition scores in a patient with hearing loss: a case report and literature review - Fang, Ke; Jiang, Da; Zhao, Minghui; Hu, Hantong; Li, Yang; Gao, Hong; Zhou, Jie (Frontiers in Neuroscience, 2025)
BackgroundSensorineural hearing loss (SNHL) is a hearing disorder caused by damage to the inner ear, the auditory centers, or the auditory nerve in the brain. Sensorineural hearing loss not only causes an increase in the pure tone audiometry of patients, but also may lead to a decrease in word recognition scores. Although contemporary medical advancements like cochlear hearing devices and auditory aids provide some assistance to individuals with hearing loss, many patients still seek more natural and non-invasive treatment options.Case presentationA 61-year-old male patient came to our acupuncture clinic on September 22, 2024, complaining of significant hearing deficit in his left ear, which had persisted for 1 year. Upon admission, pure tone audiometry showed severe hearing loss across all frequencies in the left ear, with a word recognition score of 64. Based on the comprehensive examination results, we diagnosed him with sensorineural hearing loss (SNHL). The patient had previously received both traditional Chinese and Western medical treatments at several hospitals, but his symptoms had not significantly improved. On October 20, 2024, after 11 sessions of acupuncture, the patient reported an improvement in his hearing, with the word recognition score in his left ear increasing from 64 to 76. On November 17, 2024, after completing 21 acupuncture sessions, the word recognition score in his left ear further advanced from 76 to 94. Ultimately, a two-month follow-up showed no recurrence of hearing loss.ConclusionAcupuncture might serve as a promising treatment choice for improving word recognition scores in individuals suffering from hearing loss.